EFEKTIVITAS PENINGKATAN KEMAMPUAN BERHITUNG DENGAN MENGGUNAKAN MEDIA PERMAINAN ULAR TANGGA PADA SISWA SD/MI - Dwi Ramadhani Ashary; Asmaul Husna (STKIP Subang, 2024)
The snakes and ladders game is a valuable traditional method for teaching mathematics, especially for children at the elementary school level. The aim of this research is to evaluate how the snakes and ladders game can improve the mathematics learning experience and support students in mastering numbers more effectively. The method applied in this research is a literature review, which involves analyzing various articles from Google Scholar published between 2019 and 2023 by searching using the keywords